Polymeric Desensitizer Fluororubber: A Good Binder to Improve the Thermal Stability and Mechanical Properties of 3,4-Dinitrofurazanfuroxan - Shenghui Wang; Xiaogang Mu; Yiming Luo; Ronghui Ju; Xuanjun Wang; Haixia Ma; Jijun Xiao (Molecules)
3,4-Dinitrofurazanfuroxan (DNTF) is characterized by its high energy, high detonation velocity, strong explosive power, and small critical diameter for detonation. However, its practical application is limited by poor thermal stability and mechanical properties. In this study, the polymeric desensitizer fluororubber (F2603) was introduced as a binder to enhance the overall performance of DNTF. Molecular dynamics (MD) simulations were used to investigate the thermal stability (trigger bond length and cohesive energy density (CED)) and mechanical properties, including elastic coefficient (Cij), tensile modulus (E), bulk modulus (K), shear modulus (G), Cauchy pressure (C12–C44), and Poisson’s ratio, for both pure DNTF (1 1 1) and DNTF (1 1 1)/F2603 composite systems at varying temperatures. The thermal stability was further experimentally investigated using differential scanning calorimetry (DSC) technique. The results demonstrated that the addition of F2603 leads to a shorter trigger bond length, higher CED, and a 7.2 kJ·mol−1 increase in activation energy (Ea), indicating improved thermal stability. Additionally, mechanical property simulations indicated that F2603 decreased the E, K, and G of DNTF while increasing the K/G ratio, suggesting enhanced mechanical toughness. These studies have important implications for the formulation design and practical application of DNTF and its composites.